An evaluation of the international classification of health interventions to establish its suitability for general surgery coding - Satiyadev, Sithara (My University, 2021)
Health classification systems also known as clinical coding systems are widely utilised nationally and internationally to manage healthcare delivery systems by collecting quality health data that can be communicated in a consistent, predictable and reproducible manner. Health classification systems contribute to the improvement of efficacy of healthcare by standardised recording, and analysis of healthcare data for research, patient care, disease management planning, resource and budget allocation, performance and outcomes management and reimbursement. The World Health Organisation (WHO) International Classification of Health Interventions (ICHI) has been developed for countries that lack a national intervention system or those that would like to migrate to a WHO intervention system. In its Beta-3 version, the ICHI is open to comments from healthcare stakeholders. The aim of the study was to evaluate the ICHI to establish its suitability for acute care general surgery coding from intervention data collected at three academic hospitals from the Gauteng province of South Africa. To achieve the aim, the following objectives were formulated: To evaluate the suitability of the ICHI for general surgery interventions by coding intervention descriptions extracted from a database to the ICHI codes.  To identify gaps in the ICHI system and new stem codes to address South African requirements for general surgery coding.  In relation to general surgery coding, to provide a rationale for the introduction, or rejection, of the ICHI as a nationally regulated intervention system for general surgery coding in South Africa. In meeting the objectives, the relevant literature was reviewed, the strengths, challenges and gaps in national and international classification systems were presented. Intervention data collected in a retrospective database from three academic hospitals were utilised in the assignment of the ICHI codes to establish its suitability for acute care or in hospital general surgery coding. Three clinical coders coded a sample of 3000 healthcare interventions into the ICHI codes by referencing the interventions descriptions documented by clinicians, ICD-10 codes or the radiology information. A positivist philosophy and a retrospective, descriptive study design was used to evaluate the data which allowed the research questions to be answered. Aligned to the positivistic paradigm, quantitative data analysis techniques were utilised to assess the degree of match between the intervention descriptions and the ICHI codes assigned, across the sample. The results show that the ICHI has the ability to cater for the broad range of general surgery interventions deliberated in this study, thus indicating that the ICHI is suitable for general surgery coding and can replace the multiple data coding systems in South Africa for general surgery. To support the effective implementation of the ICHI, healthcare documentation needs to improve, coders need to be trained, and accredited and national ICHI standards and guidelines need to be developed. The detailed illustration of the various challenges and limitations in the assignment of the ICHI codes and the in-depth explanation of the recommendations, makes an invaluable contribution to the adoption and implementation of the ICHI as a national intervention coding system for general surgery.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy